2014
DOI: 10.18632/oncotarget.2173
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of selective inhibitors of Glutaminase-2, which inhibit mTORC1, activate autophagy and inhibit proliferation in cancer cells

Abstract: Glutaminase, which converts glutamine to glutamate, is involved in Warburg effect in cancer cells. Two human glutaminase genes have been identified, GLS (GLS1) and GLS2. Two alternative transcripts arise from each glutaminase gene: first, the kidney isoform (KGA) and glutaminase C (GAC) for GLS; and, second, the liver isoform (LGA) and glutaminase B (GAB) for GLS2. While GLS1 is considered as a cancer therapeutic target, the potential role of GLS2 in cancer remains unclear. Here, we discovered a series of alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…While this report is at odds with previous literature and the predicted localization of either LGA isoform, no study has yet been published which either disputes or supports these findings. The N-terminal residues of the longer LGA isoform are truncated following mitochondrial localization, but it is currently unclear if a similar tr uncation occurs for the shorter LGA variant [51,58].…”
Section: Gls 5ǵmentioning
confidence: 99%
See 1 more Smart Citation
“…While this report is at odds with previous literature and the predicted localization of either LGA isoform, no study has yet been published which either disputes or supports these findings. The N-terminal residues of the longer LGA isoform are truncated following mitochondrial localization, but it is currently unclear if a similar tr uncation occurs for the shorter LGA variant [51,58].…”
Section: Gls 5ǵmentioning
confidence: 99%
“…The same group later demonstrated that transfection of the same cells with LGA increases their susceptibility to alkylating agents, by downregulating the DNA repair gene MGMT [116]. However, Lee et al showed that LGA inhibition or genetic silencing inhibited the growth of both A549 lung cancer cells and HepG2 hepatoma cells [58].…”
mentioning
confidence: 99%
“…There exist two glutaminases, GLS (kidney type KGA and GAC isoforms) and GLS2 (liver isoform (LGA) and glutaminase B (GAB)), yet GLS is the isoform upregulated in cancer, as well as the main glutaminase within the kidney(25,26). Since GSH synthesis requires glutamate in addition to glycine and cysteine, we tested the hypothesis that blocking glutamate production from glutamine by GLS inhibition will down-regulate this important antioxidant pathway, resulting in higher ROS levels, which will be selectively toxic to cancer cells due to their increased local ROS levels.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the metabolic rewiring shown by cancer cells involves not only the Warburg effect with enhanced glycolysis and high glutamine consumption, but also elevated rates of lipid biosynthesis, maintenance of redox homeostasis and limited levels of autophagy in the first steps of oncogenesis [1012]. Recent evidence has shown that cancer cells can engage glutamine metabolism enzymes, such as PEP-carboxykinase (PCK2) [13] or pyruvate carboxylase (PC) [14], to develop metabolic adaptation and promote enhanced cell growth when even glucose is limited. In addition, they can activate autophagy when glutamine is inhibited [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has shown that cancer cells can engage glutamine metabolism enzymes, such as PEP-carboxykinase (PCK2) [13] or pyruvate carboxylase (PC) [14], to develop metabolic adaptation and promote enhanced cell growth when even glucose is limited. In addition, they can activate autophagy when glutamine is inhibited [15]. Furthermore, metabolites, such as ATP, acetyl-CoA (AcCoA), reactive oxygen species (ROS) and enzymes with key role in metabolic regulation may act on different signaling pathways controlling tumor growth [9, 1619].…”
Section: Introductionmentioning
confidence: 99%